# Multiply polynomials

## Question 25: Reducing the expression we (7 x(x+1)-3 x(1-x)) gets

Question 25: Reducing the expression we (7 x(x+1)-3 x(1-x)) gets A. (- x^{2}+4 x ) B. (3x^{2}+4 x ) C. (7x^{2}+4 x ) D. (10 x^{2}+4 x ) We have (7 x(x+1)-3 x(1-x)=7 x^{2}+7 x-3 x+3 x^{2}=10 x^{2}+4 x . ) =============== Go to Source

## Question 26: Reducing the expression (x^{2}(x+3)-x(x-2)) we get

Question 26: Reducing the expression (x^{2}(x+3)-x(x-2)) we get A. (-3x^{3}+ x^{2}+2 x +1) B. (x^{3}-5 x^{2}+ x ) C. (-2x^{3}+4 x^{2}+2 x ) D. (x^{3}+2 x^{2}+2 x ) We have (x^{2}(x+3)-x(x-2)=x^{3}+3 x^{2}-x^{2}+2 x=x^{3}+2 x ^{2}+2 x ) =============== Go to Source

## Question 11: Reducing the expression ((5-x)(x+1)-3 xleft(x^{2}-2right)) we get

Question 11: Reducing the expression ((5-x)(x+1)-3 xleft(x^{2}-2right)) we get A. (3 x^{3}- x^{2}+4 x+1 ) B. (2x^{3}+3 x^{2}+4 x+5 ) C. (-3 x^{3}+5 x^{2}) D. (-3 x^{3}+5 x^{2}+4 x+5 ) ((5-x)(x+1)-3 xleft(x^{2}-2right)=5 x+5-x^{2}-x-3 x^{3}+6 x^{2}=-3 x^{3}+5 x^{2}+4 x+5 ) =============== Go to Source

## Question 12: Reducing the expression (frac{1}{2}(x+1)(x-3)) we get

Question 12: Reducing the expression (frac{1}{2}(x+1)(x-3)) we get A. (frac{1}{2} x^{2}-x-frac{3}{2} ) B. (x^{2}-x-frac{3}{2} ) C. (frac{3}{2} x^{2}-x-frac{3}{2} ) D. ( x^{2}-x-3) (frac{1}{2}(x+1)(x-3)=left(frac{1}{2} x+frac{1}{2}right)(x-3)= frac{1}{2} x^{2}-frac{3}{2} x+frac{1}{2} x-frac{3}{2}=frac{1}{2} x^{2}-x-frac{3}{2} ) =============== Go to Source

## Question 10: Reducing the expression ((7-2 x) cdot x-(x+1)(x-2)) we get

Question 10: Reducing the expression ((7-2 x) cdot x-(x+1)(x-2)) we get A. (2 x^{2}+3x ) B. (-3 x^{2}+3 x) C. (-3 x^{2}+8 x+2 ) D. (-3 x^{2}+8 x) ((7-2 x) cdot x-(x+1)(x-2)=left(7 x-2 x^{2}right)-left(x^{2}-2 x +x-2right)=7 x-2 x^{2}-x^{2}+2 x-x+2=-3 x^{2}+8 x+2 ) =============== Go to Source

## Question 10: Performing the calculation ((-5 x y+1)(x-1)) we get:

Question 10: Performing the calculation ((-5 x y+1)(x-1)) we get: A. (-5 x^{2} y+5 x y+x-1 ) B. (2 x^{2} y+5 x y+x-1 ) C. (-3 x^{2} y+4 x y+x-1 ) D. (-3 x^{2} y- x y+x ) We have ((-5 x y+1)(x-1)=-5 x^{2} y+5 x y+x-1 ) =============== Go to Source

## Question 5: Performing the calculation (-x(x+1)(x-5)) we get:

Question 5: Performing the calculation (-x(x+1)(x-5)) we get: A. (-x^{3}+ x^{2}+5 x ) B. (-x^{3}+4 x^{2}+5 x ) C. (2x^{3}+4 x^{2}+5 x +1) D. (x^{3}+2x^{2}+5 x ) (-x(x+1)(x-5)=left(-x^{2}-xright)(x-5)=-x^{2} cdot x+5 x^{2 }-x-x+5 x=-x^{3}+4 x^{2}+5 x ) =============== Go to Source

## Question 8: Performing the calculation (left(x+frac{1}{2}right)(3 x-1)) we get:

Question 8: Performing the calculation (left(x+frac{1}{2}right)(3 x-1)) we get: A. (3 x^{2}+frac{3}{2} x-frac{1}{2} ) B. (x^{2}+frac{1}{2} x-frac{1}{2} ) C. ( x^{3}+frac{1}{2} x-frac{1}{2} ) D. (3 x^{2}+frac{1}{2} x-frac{1}{2} ) We have (left(x+frac{1}{2}right)(3 x-1)=3 x^{2}-x+frac{3}{2} x-frac{1}{2} =3 x^{2}+frac{1}{2} x-frac{1}{2} ) =============== Go to Source

## Question 3: Performing the calculation ((-x+2 y)(x-1) ) we get:

Question 3: Performing the calculation ((-x+2 y)(x-1) ) we get: A. (-x^{2}+x+2 x y-2 y +1) B. (-3x^{2}+x+ x y-2 y . ) C. (3x^{2}+x-2 x y-2 y . ) D. (-x^{2}+x+2 x y-2 y . ) ((-x+2 y)(x-1) =-x^{2}+x+2 x y-2 y . ) =============== Go to Source

## Question 4: Performing the calculation (left(frac{1}{3} xyright)(x+y)) we get:

Question 4: Performing the calculation (left(frac{1}{3} xyright)(x+y)) we get: A. (frac{1}{3} x^{2}-frac{1}{3} x yy^{2}) B. ( x^{2}-frac{2}{3} x yy^{2}) C. (-2 x^{2}-frac{2}{3} x yy^{2}) D. (frac{1}{3} x^{2}-frac{2}{3} x yy^{2}) (left(frac{1}{3} xyright)(x+y)=frac{1}{3} x^{2}+frac{1}{3} x yx yy^{ 2}=frac{1}{3} x^{2}-frac{2}{3} x yy^{2}) =============== Go to Source